PENGARUH KINERJA KEUANGAN TERHADAP PANGSA PASAR BANK UMUM SYARIAH DI INDONESIA PERIODE 2016-2020 - Wahyuni, Sri (Al-Qashdu : Jurnal Ekonomi dan Keuangan Syariah, 2023)
The aim of this research is to examine how Sharia Commercial Banks in Indonesia are finalized and their relationship to market share. This research uses quantitative descriptive methods and collects data through secondary data or through quarterly financial reports of Sharia Commercial Banks. The population in this research is the Financial Reports of Sharia Commercial Banks in Indonesia for the 2018-2022 period. The sampling technique in this research is total sampling, namely a sampling method known as total sampling using a proportional number of samples with a population of less than 100. Total sampling is carried out because the entire population functions as a research sample for all. The research results show that there is a negative and significant effect of FDR on the market share of Sharia Commercial Banks, CAR has no effect on the market share of Sharia Commercial Banks, DER has a positive and significant effect on the market share of Sharia Commercial Banks, ROA has a positive and significant effect on the market share of Sharia Commercial Banks.Keywords:  FDR; CAR; DER; ROA; Sharia Commercial Bank Market Share